Why are they always older and stronger? Relative age effect and talent identification factors in youth elite soccer players - Rubajczyk, K. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Assessment of the players motor potential for soccer is multidimensional. In most cases, testing set dedicated to youth players take into account the anthropometric, linear or curve sprinting characteristics, jumping and agility testing and the ability to rapidly change direction. Nevertheless, interpretation of the obtained data is disturbed by the phenomenon of relative age effect (RAE) and different maturity statuses in youth soccer players. There is a lack of studies that investigated the relationship between anthropometric profile, body composition, results of motor tests, and different methods of maturity-based banding for the Talent Identification (TI) process in soccer. The aims of the study were: a) examination of anthropometrical and motor performance with traditional age-grouping by chronological age (CA) and Midway Point methods (MP) proposed by Helsen and colleagues (2021), and b) identify the birth-date distribution in elite polish youth soccer payers.